Demand for biodiversity protection and carbon storage as drivers of global land change scenarios. (September 2016) - Eitelberg, David A.; van Vliet, Jasper; Doelman, Jonathan C.; Stehfest, Elke; Verburg, Peter H.
Highlights: We present global land change scenarios driven by carbon storage, biodiversity, and food. Carbon storage and biodiversity demands greatly influence future land change. Incorporating additional demands for land leads to specialization of land systems. Demand for ecosystem services will increasingly influence land change. Abstract: Many global land change scenarios are driven by demand for food, feed, fiber, and fuel. However, novel demands for other ecosystem services give rise to nexus issues and can lead to different land system changes. In this paper we explore the effects of including multiple different demands in land change scenarios. Our reference scenario is driven by demands for crop production, ruminant livestock production, and provisioning of built-up area. We then compare two alternative scenarios with additional demands for terrestrial carbon storage and biodiversity protection, respectively. These scenarios represent possible implementations of globally agreed policy targets. The simulated land system change scenarios are compared in terms of changes in cropland intensity and area, as well as tree and grassland area changes. We find that the carbon and biodiversity scenarios generally result in greater intensification and less expansion of cropland, with the biodiversity scenario showing a stronger intensification effect. However, the impact of setting the targets impacts different world regions in different ways. Overall, both scenarios result in a larger tree area compared to the reference scenario, while the carbon scenario also yields more grassland area. The land systems simulated while accounting for these additional demand types show strong patterns of specialization and spatial segregation in the provisioning of goods and services in different world regions. Our results indicate the relevance of including demands for multiple different goods and services in global land change assessments.